Intercultural Communication And Working Women's Health In Balaraja - Ummanah; Yuliati; Jatayu Hadi Prakoso; Bayquni (Journal of Communication and Social Sciences, 2026)
Working women in industrial areas such as Balaraja District, Tangerang Regency, face intercultural communication challenges in the domestic sphere because labor mobility brings together spouses from different cultural backgrounds. These differences may intensify role conflict and affect reproductive health management and mental health in the digital era. This study examined the effects of intercultural communication, digital literacy, and domestic workload on working women’s health. A quantitative explanatory survey involved 50 married working women selected through purposive sampling. Data were analyzed using descriptive statistics, instrument validity and reliability tests, correlation analysis, and multiple regression. Intercultural communication positively affected mental health (β = 0.42; p = 0.003) and reproductive health management (β = 0.35; p = 0.011). Digital literacy also had a positive effect (β = 0.29; p = 0.027), whereas domestic workload negatively affected mental health (β = -0.38; p = 0.005). Supportive intercultural family communication, equitable domestic role negotiation, and effective digital health literacy are therefore important for improving working women’s well-being in industrial communities. However, the smaller digital-literacy coefficient indicates that access to digital technology or health information alone is insufficient unless it is supported by healthy communication negotiation, partner responsiveness, and equitable household arrangements.